Penyuluhan dan Pelatihan Penerapan 5M dalam Beradaptasi Covid-19 - Ernasari E; Haeril Amir; Suhermi S; Try Ayu Patmawati; Syaiful S (PT.Mantaya Idea Batara, 2022)
Who has declared covid-19 a global health emergency. Diseases due to covid-19 virus infection can cause mild moderate respiratory infections, severe and even to eliminate the life of sufferers. Until now the number of cases in Indonesia confirmed positive until July 23, 2021 is 3,033,339 people with the number of deaths 79,032 people. The application of 5M in everyday life can reduce exposure and increase the rate of covid-19. Various violations of the implementation of health protocols are still common in various areas, although raids are often carried out by officers. This incompatibility is what makes the transmission of the virus more rapidly widespread. The 3M movement is felt less because the number of covid exposure continues to increase. Other efforts can be done by doing Health counseling and 5M Application training. The methods used are lectures, lectures and demonstrations. Activities are carried out for 3 sessions with a duration of 30 minutes for each session. The results achieved, namely the improvement of people's knowledge and skills in the application of 5M in adapting covid-19. It is expected that the implementation of 5M continues to be improved in everydays life.